Jane Austen's letters - Austen, Jane, 1775-1817.; Le Faye, Deirdre (Oxford [England] ; New York : Oxford University Press, 2011)
This fourth edition incorporates the findings of new scholarship to enrich our understanding of Austen and give us the fullest and most revealing view yet of her life and family. There is a new preface, the biographical and topographical indexes have been amended and updated, a new subject index has been created, and the contents of the notes added to the general index.
Includes bibliographical references (p. 471-481) and indexes.
Keywords: Austen, Jane, -- 1775-1817; Novelists, English -- 19th century -- Correspondence; Women novelists, English -- 19th century -- Correspondence; Austen, Jane